Whole Transcriptome Profiling of the Effects of Cadmium on the Liver of the Xiangxi Yellow Heifer - Wei, Yameng; Yi, Kangle; Shen, Caomeihui; Chen, Xue; Iqbal, Tariq; Cao, Maosheng; Chen, Tong; Luo, Yang; Li, Jianbo; Zhou, Xu; Li, Chunjin; Chen, Lu (Frontiers in Veterinary Science, 2022)
Cadmium (Cd) is a toxic heavy metal with high mobility in soil and enters human and animal bodies through the food chain. The toxic effects of Cd on the liver were investigated by whole-transcriptome sequencing (RNA-seq) of liver tissues of Xiangxi heifer fed Cd-exceeding diets. A total of 551 differentially expressed mRNAs (DEmRNA), 24 differentially expressed miRNAs (DEmiRNA) and 169 differentially expressed LncRNAs (DELncRNA) were identified (P<0.05, |log2FC|>1). On the basis of DEGs, the differentially expressed genes were analyzed by gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG ) enrichment analysis of differentially expressed genes. Overall, we found that under Cd exposure DEGS was enriched to the AMPK pathway involved in autophagy regulation and the PPAR pathway involved in lipid metabolism. In addition, among DEmRNAs, APOA4 gene which have anti-inflammatory and antioxidant effects, anti-apoptotic gene ATP12A and Cholesterol metabolism-associated gene LIPG were significantly down-regulated. CXCL3, CYP7A1 and SCD which involved in fatty liver development were significantly up-regulated. The main effects of Cd on the liver of Xiangxi yellow heifers were revealed by these genes. The differential genes involved in the results of this study may provide useful biomarkers for the prediction and treatment of Cd-related diseases in the future.